2023
DOI: 10.1021/jacs.2c13630
|View full text |Cite
|
Sign up to set email alerts
|

Anion Intercalation into Graphite Drives Surface Wetting

Abstract: The unique layered structure of graphite with its tunable interlayer distance establishes almost ideal conditions for the accommodation of ions into its structure. The smooth and chemically inert nature of the graphite surface also means that it is an ideal substrate for electrowetting. Here, we combine these two unique properties of this material by demonstrating the significant effect of anion intercalation on the electrowetting response of graphitic surfaces in contact with concentrated aqueous and organic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 85 publications
(160 reference statements)
1
18
0
Order By: Relevance
“…In addition, we also found evidence of the intercalated Cl ions into the HOPG galleries via XPS analysis, as shown in Figures S5 and S6. However, all the studies focus on the anion intercalation-driven electrowetting on the HOPG substrate only qualitatively but do not explain any electrowetting response behavior, especially the nonintercalation of cation, at the same voltage range with negative polarity. ,, …”
Section: Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, we also found evidence of the intercalated Cl ions into the HOPG galleries via XPS analysis, as shown in Figures S5 and S6. However, all the studies focus on the anion intercalation-driven electrowetting on the HOPG substrate only qualitatively but do not explain any electrowetting response behavior, especially the nonintercalation of cation, at the same voltage range with negative polarity. ,, …”
Section: Results and Discussionmentioning
confidence: 99%
“…reported threshold voltage-dependent electrowetting response behavior for Cl – anion intercalation for the positive polarity applied to the substrate. Despite the fact that many groups have advanced their understanding and applications of graphite ion intercalation-based electrowetting, their work did not reveal the underlying cause of these phenomena. , These unresolved issues inspired us to utilize the EWOC approach to reveal the underlying mechanism of the dependence of hydration energy and hydration shell size on the intercalation of ions into the graphite layers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, we observed that below 2 V vs. Ag/AgCl (KCl 3 M) the intercalation step results in yields with low efficiency for the global process and that the current value increases with higher potentials (E E ), indicating an enhancement in SO 2À 4 intercalation at elevated potentials with the resulting increase in the graphite surface area due to the exfoliation of GO flakes, as reported in previous literature. [43][44][45] The method proposed in this study offers several advantages over traditional and other electrochemical methods. It operates under moderate reaction conditions, requires short processing times, is relatively cost-effective, and is environmentally friendly, as it avoids generating toxic or hazardous waste.…”
Section: Resultsmentioning
confidence: 99%
“…25 Several interesting recent studies on graphite/graphene electrodes indicate a decrease in the contact angle upon cation or anion insertion in both aqueous and non-aqueous electrolytes akin to our observations. 25–30 EIS measurements (Fig. S15, ESI†) also show that the charge transfer resistance for the natural graphite electrode is much lower in comparison to the pyrolytic graphite electrode.…”
mentioning
confidence: 98%